2008
DOI: 10.1159/000117800
|View full text |Cite
|
Sign up to set email alerts
|

Whole Blood Assays to Identify Th1 Cell Antigens and Peptides Encoded by <i>Mycobacterium tuberculosis</i>-Specific RD1 Genes

Abstract: Objective: To identify Th1 cell-stimulating antigens/peptides encoded by the genes predicted in the Mycobacterium tuberculosis-specific genomic region of difference (RD)1, deleted in Mycobacterium bovis Bacille Calmette-Guérin(BCG), by using synthetic peptides and whole blood from tuberculosis (TB) patients. Materials and Methods: Heparinized peripheral blood was obtained from culture-proven pulmonary TB patients (n = 16) attending the Chest Disease Hospital, Kuwait. Whole blood was diluted with tissue culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…These results suggest that only RD1 contains immunodominant antigens. It has been shown that the RD1 genomic region of M. tuberculosis has three major T-cell antigens, i.e., PPE68, ESAT6, and CFP10 (18,28). When tested alone, ESAT6 and CFP10 induce strong antigen-induced proliferation and IFN-␥ responses in TB patients but weak responses in M. bovis BCG-vaccinated healthy subjects residing in Kuwait, which could be attributed to previous exposure to M. tuberculosis (2,3,4,26,32), whereas, PPE68 induces strong responses in both TB patients and M. bovis BCG-vaccinated healthy subjects (32).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that only RD1 contains immunodominant antigens. It has been shown that the RD1 genomic region of M. tuberculosis has three major T-cell antigens, i.e., PPE68, ESAT6, and CFP10 (18,28). When tested alone, ESAT6 and CFP10 induce strong antigen-induced proliferation and IFN-␥ responses in TB patients but weak responses in M. bovis BCG-vaccinated healthy subjects residing in Kuwait, which could be attributed to previous exposure to M. tuberculosis (2,3,4,26,32), whereas, PPE68 induces strong responses in both TB patients and M. bovis BCG-vaccinated healthy subjects (32).…”
Section: Discussionmentioning
confidence: 99%
“…The complex mycobacterial antigens used in this study were irradiated whole-cell M. tuberculosis H37Rv [18] , MTCF enriched for secreted antigens and purified M. tuberculosis cell walls [19] .…”
Section: Complex and Purified Single Antigens Of M Tuberculosismentioning
confidence: 99%
“…The complex mycobacterial antigens used in this study were irradiated whole-cell M. tuberculosis H37Ra and M. bovis BCG (29,50), M. tuberculosis culture filtrate (MT-CF) enriched for secreted antigens, and purified M. tuberculosis cell walls (MT-CW) (48). MT-CF and MT-CW were kindly provided by J. T. Belisle (Colorado State University, Fort Collins, CO).…”
Section: Methodsmentioning
confidence: 99%